Person- centred communication Theory and Practice 1998 - Antoinette Gmeiner (AOSIS, 1998)
Person- centred communication offers helping professionals an understanding of the theory, practice, and value base that underline a person- centred approach in helping people. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.